Development of Asbestos-free Disc Brake Pad Using Periwinkle Shell Powder and Coconut Shell Ash as Base Materials - Mawuli, Seckley Emmanuel; Anthony, Simons; Akintunde, Dahunsi Olurotimi (European Journal of Applied Sciences, 2022)
Brake pads are integral part of an automobile braking system that contribute to the full control of the vehicle. The composite materials for their production must therefore possess adequate chemical, mechanical, physical, and thermal properties. The development of asbestos-free disc brake pad using Periwinkle Shell (PS) powder and Coconut Shell Ash (CSA) as reinforcement and frictional filler material respectively is presented. This was done with a view of establishing suitability of PS powder and CSA as replacements for asbestos which has been found to be carcinogenic and capable of causing Asbestosis and Mesothelioma [1]. Other ingredients used are graphite as lubricant, epoxy resin as binder, copper, zinc, and aluminum powders as abrasives and also to impact mechanical strength. The optimum percentage formulation of these materials for the pad was arrived at by using the ANOVA tool of the Box-Behnken technique of Design Expert Software, DX-13. The CSA and PS powders were sieved into grades of 106 µm, 150 µm, 212 µm and 300 µm and then combined with other constituents to produce the brake pad. The pads were characterized in terms of their physical, mechanical and tribological properties. It was observed that increase in particle size distributions leads to decrease in densification and carbon crosslinking of the produced composite brake pads. Therefore, the 106 µm particle size sample has better properties than others. Comparison analysis shows that the performance parameters of the 106 μm size brake pad compares well, and in some cases better, with typical after-market replacement pads, an asbestos-based brake pad and brake pads developed from past research works.